Adherens, tight, and gap junctions in ependymal cells: A systematic review of their contribution to CSF-brain barrier - Serra, Riccardo; Simard, J. Marc (Frontiers in Neurology, 2023)
Introduction The movement of fluids and solutes across the ependymal barrier, and their changes in physiologic and disease states are poorly understood. This gap in knowledge contributes strongly to treatment failures and complications in various neurological disorders. Methods We systematically searched and reviewed original research articles treating ependymal intercellular junctions on PubMed. Reviews, opinion papers, and abstracts were excluded. Research conducted on tissue samples, cell lines, CSF, and animal models was considered. Results A total of 45 novel articles treating tight, adherens and gap junctions of the ependyma were included in our review, spanning from 1960 to 2022. The findings of this review point toward a central and not yet fully characterized role of the ependymal lining ultrastructure in fluid flow interactions in the brain. In particular, tight junctions circumferentially line the apical equator of ependymal cells, changing between embryonal and adult life in several rodent models, shaping fluid and solute transit in this location. Further, adherens and gap junctions appear to have a pivotal role in several forms of congenital hydrocephalus. Conclusions These findings may provide an opportunity for medical management of CSF disorders, potentially allowing for tuning of CSF secretion and absorption. Beyond hydrocephalus, stroke, trauma, this information has relevance for metabolite clearance and drug delivery, with potential to affect many patients with a variety of neurological disorders. This critical look at intercellular junctions in ependyma and the surrounding interstitial spaces is meant to inspire future research on a central and rather unknown component of the CSF-brain interface.